The impact of reducing the pension generosity on inequality and schooling - Miguel Sanchez-Romero; Alexia Fürnkranz-Prskawetz (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2019)
In this paper we investigate the impact of a reduction in the pension replacement rate on the schooling choice and on inequality. We develop an overlapping generations model in which individuals differ by their life expectancy and in the cost of attending schooling. Individuals optimally choose their consumption path and their educational attainment. Within our framework we first show how many progressive pension systems are ex ante regressive due to the difference in life expectancy across skill groups and, second, we derive the level of progressivity that restores an equal treatment of the pension system across skill groups.
Keywords: E24; J10; J18; H55; 330; Human capital; Longevity; Inequality; Life cycle; Social security; Pension; Progressivity